Fungal endophytes from Thalassia testudinum show bioactivity against the seagrass pathogen, Labyrinthula spp. - Ugarelli, Kelly; Jagels, Annika; Choi, Chang Jae; Loesgen, Sandra; Stingl, Ulrich (Frontiers in Marine Science, 2024)
Thalassia testudinum has undergone die-offs in the past century due to seagrass wasng disease caused by Labyrinthula sp. Litle is known about how seagrasses resist Labyrinthula infecons, but metabolites that inhibit Labyrinthula were previously extracted from seagrass leaves. Furthermore, leaf fungal endophytes from seagrasses possess anpathogenic potenal, but their acvity against Labyrinthula is unknown. Here, we aimed to idenfy whether fungal endophytes of T. testudinum can aid in disease defense against Labyrinthula. Through Illumina amplicon sequencing of the leaves' mycobiome, we idenfied fungi that are known to produce anmicrobials. We also isolated and extracted organic compounds from endophytes to test their an-Labyrinthula potenal using disk diffusion assays. Twentytwo isolates inhibited Labyrinthula, from which two isolates, Trichoderma sp. P1a and Diaporthe sp.M14, displayed strong inhibion. LC-HRMS/MS analysis determined the likely bioacve compounds of Trichoderma as peptaibols, and of Diaporthe as cytosporone B. Cytosporone B was confirmed bioacve against Labyrinthula via disk diffusion assays. While these organisms are low in abundance in the mycobiome, this study demonstrates that seagrass endophytes have the potenal to play an important role in defense against Labyrinthula.